Socio-demographic Characteristics and Psychosocial Stressors in the Children and Adolescents with Somatoform Disorders - Jalan, Rekha K.; Adhikari, Jyoti; Belbase, Mohan (Journal of Nepalgunj Medical College, 2019)
Introduction: Somatoform disorders are characterized by physical symptoms that suggest a medical condition, and which are not fully explainable by general medical condition, or by the direct effects of a substance, or by another mental disorder. Objectives: to study the socio-demographic characteristics and psychosocial stressors in children and adolescents with somatoform disorders. Methods: From 1st January, 2018 to 30th June 2018, Children and adolescents from 3 to 18 years of age with unexplained physical st thsymptoms were evaluated using DSM – IV criteria. Detailed evaluation followed for those meeting inclusion criteria. Results: Among 65 patients (18, 27.69% boys and 47, 72.31% girls) meeting inclusion criteria, conversion disorder was the most common (37, 56.92%), followed by undifferentiated somatoform disorder (15, 23.08%). Girls were significantly more represented among conversion disorder patients compared to other groups of somatoform disorders (68.08% vs. 27.78%, X2 =8.63, p<0.01) Stressors 2 were identified in 95% and acute precipitating stressors were present in 75% patients. Both the boys and girls had significantly higher rates of academic problems. Boys found to have social and environmental problems while girls had problems in primary support group. Conclusion: Somatoform disorder, particularly conversion disorder is more common and it is found more in girls. Academic problems, poor interpersonal relations and conflict in the family are the important psychosocial stressors.